Islamic Parenting Guidance to Improve Parenting Abilities in Instilling Religious and Moral Values (Research at the Alfani Arjasari Islamic Education Foundation Bandung) - Rifa Fitriannisa; Lilis Satriah; Hajir Tajiri (al-Afkar, Journal For Islamic Studies, 2024)
This research stems from the cases involving minors, such as sexual abuse and bullying, which are often linked to ineffective parenting practices. These issues contribute to a decline in children's spiritual and moral values. Thus, enhancing parents' skills in instilling religious and moral principles becomes crucial. The study aims to explore the Islamic parenting guidance program designed to improve parents' ability to teach religious and moral values, the implementation process of the program, the outcomes of parents' skills following the program, and the development of an intrinsic guidance model. The research was carried out at the Alfani Islamic Education Foundation (YPI Alfani) and Arjasari in Bandung Regency, using a field research approach with descriptive qualitative methods. The researcher engaged with school principals, teachers, and parents through observation, interviews, and documentation. Data analysis involved three steps: data reduction, presentation, and conclusion. Triangulation techniques were applied to ensure the credibility of the data. The results showed a significant improvement in parents' parenting abilities, allowing them to adopt more effective approaches in imparting religious and moral education. Additionally, intrinsic models for enhancing the program's implementation were developed based on the findings.